A Woman's Place is in the Resistance: The Power of the Female Role Model - Stottlemyer, Kelsey Taryn Kuszmaul (My University, 2022)
What makes a good role model? The women’s marches that took place beginning in 2017 provide us with a somewhat unexpected answer. These marches not only protested the election of the 45th President of the United States but also spoke out against the ways that women’s autonomy and voices have been threatened around the world. Marchers lifted protest signs depicting strong, independent, iconic women to support their message, including a variety of figures from pop culture who have refused to accept the injustices that they face in their own fictional worlds. These signs helped to give the marchers’ message another level of meaning. This paper will consider three famous female characters who appeared repeatedly on these protest signs: Wonder Woman (from DC Comics), Princess Leia (from the Star Wars saga) and Hermione Granger (from the Harry Potter series). These three figures are valuable role models for women because they exhibit kindness, intelligence, wit, and a passion for justice—even in the face of insurmountable odds. Thus, they serve as tangible examples for a global community looking to spread a message of hope and equity and to inspire others to stand up for women’s rights.
Keywords: Pop Culture; Protest; Global Feminism; Women's March; Wonder Woman; Princess Leia; Hermione Granger